Synapsin Isoforms Regulating GABA Release from Hippocampal Interneurons - Song, Sang-Ho (2016)
Although synapsins regulate GABA release, it is unclear which synapsin isoforms are involved. We identified the synapsin isoforms that regulate GABA release via rescue experiments in cultured hippocampal neurons from synapsin I, II, and III triple knock-out (TKO) mice. In situ hybridization indicated that five different synapsin isoforms are expressed in hippocampal interneurons. Evoked IPSC amplitude was reduced in TKO neurons compared with triple wild-type neurons and was rescued by introducing any of the five synapsin isoforms. This contrasts with hippocampal glutamatergic terminals, where only synapsin IIa rescues the TKO phenotype. Deconvolution analysis indicated that the duration of GABA release was prolonged in TKO neurons and this defect in release kinetics was rescued by each synapsin isoform, aside from synapsin IIIa. Because release kinetics remained slow, whereas peak release rate was rescued, there was a 2-fold increase in GABA release in TKO neurons expressing synapsin IIIa. TKO neurons expressing individual synapsin isoforms showed normal depression kinetics aside from more rapid depression in neurons expressing synapsin IIIa. Measurements of the cumulative amount of GABA released during repetitive stimulation revealed that the rate of mobilization of vesicles from the reserve pool to the readily releasable pool and the size of the readily releasable pool of GABAergic vesicles were unaffected by synapsins. Instead, synapsins regulate release of GABA from the readily releasable pool, with all isoforms aside from synapsin IIIa controlling release synchrony. These results indicate that synapsins play fundamentally distinct roles at different types of presynaptic terminals.